The Moderating Role of Training in The Relationship Between Leadership Implementation of Quality Management and Lecturers' Performance: A Case Study in Egypt Higher Education Institutions - Shorouk Aboudahr; Mua’azam Mohamad; Khaliza Saidin (Journal of Pedagogy and Education Science, 2023)
To implement quality management under uncertainty, higher education institutions should explore factors influencing lecturers' performance This study assess the moderating role of training in the relation of leaders’ implementations of quality management to lecturers' performance among lecturers in Egyptian higher education institutions. The data for this aim was obtained through self-administered questionnaires from the public university of Egypt and applied PLS software to analyze the data. The questionnaire data were obtained from 310 lecturers who confirm hypotheses that training strengthens the positive relationship between leaders’ implementations of quality management on lecturers' performance.  The findings showed that leaders' implementation of quality management and training had significant predictions on lecturer’s performance. Furthermore, the interaction item between leaders’ implementation of quality management and training could significantly affect lecturers’ performance. This indicated that the association between implementation of quality management and lecturers’ performance could be moderated by training. In the light of the research results, this study provides a special perspective for educators, practitioners, and researchers to recognize the role of training in promoting lecturers’ higher levels of performance in higher education contexts.